2006
DOI: 10.1634/stemcells.2005-0521
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Differentiation of Human Placenta‐Derived Multipotent Cells into Hepatocyte‐Like Cells

Abstract: Multipotent cells isolated from human term placenta (placenta-derived multipotent cells [PDMCs]) have been known to be able to differentiate into mesodermal lineage cells, including adipocytes and osteoclasts. The low infection rate and young age of placenta compared with other tissue origins of adult stem cells make theses cells attractive target for cell-based therapy. However, the differentiation potential of PDMCs toward hepatic cells has not been evaluated yet. In this study, we cultivated PDMCs with hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(105 citation statements)
references
References 61 publications
3
99
0
2
Order By: Relevance
“…Banas et al (2007) reported hepatogenic differentiation of AT-MSCs from CD105 + AT-MSCs. Other MSCs from amniotic fluid and placenta have been also reported to differentiate into functional HLCs (Chien et al, 2006;de Coppi et al, 2007). In this study, MenSCs were induced to differentiate into heoatocytes with a cocktail of HGF, FGF-4, and OSM (Chen et al, 2007;Li J. et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Banas et al (2007) reported hepatogenic differentiation of AT-MSCs from CD105 + AT-MSCs. Other MSCs from amniotic fluid and placenta have been also reported to differentiate into functional HLCs (Chien et al, 2006;de Coppi et al, 2007). In this study, MenSCs were induced to differentiate into heoatocytes with a cocktail of HGF, FGF-4, and OSM (Chen et al, 2007;Li J. et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Though constantly under debate, there are accumulating evidences over the years supporting the hepatic transdifferentiation from MSC of different origins [5][6][7][8]. These hepatocyte-like cells transdifferentiated from MSC closely resemble hepatocyte characteristics in vitro.…”
Section: Induced Pluripotent Stem Cells (Ip-mentioning
confidence: 95%
“…Transcriptional activation by HNF4␣ is mediated by its binding as a homodimer to direct repeat-1 promoter sequences of target genes (5). Genes transactivated by HNF4␣ encode various transcription factors, enzymes, and proteins involved in numerous processes, including hematopoiesis, blood coagulation/fibrinolysis, together with liver development and function (5)(6)(7)(8)(9). Conversely, molecular defects in HNF4␣ expression may provoke major disorders as noted in late-onset type 2 diabetes (10, 11) as well as in maturity-onset diabetes of the young 1, a disorder characterized by autosomal dominant inheritance and impaired glucose-stimulated insulin secretion from pancreatic ␤-cells (12,13).…”
mentioning
confidence: 99%